1980
DOI: 10.1677/joe.0.0870047
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Receptors in the Rat Kidney

Abstract: Specific binding of 125I-labelled ovine prolactin iodinated by a lactoperoxidase method was demonstrated in crude membrane preparations of kidneys and adrenals of male Sprague-Dawley rats and livers from female rats. Membrane preparations derived from the 100,000 g fractions of tissue homogenates contained most of the specific prolactin binding. Kinetic and affinity characteristics of prolactin binding to kidney membranes were examined in detail. Maximal specific binding occurred after incubation for 30 h at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…PRL contributes to the control of salt and water metabolism in mammals [1], and specific uptake of 1251-labeled ovine PRL was seen in proximal tubular cells in rats [40]. In situ hybridization with oligonucleotide probes complementary to PRLRs and PRLRL indicated the localization of both receptor mRNAs in the kidney [13,141, although there was a large discrepancy in the distribution of signals.…”
Section: Discussionmentioning
confidence: 99%
“…PRL contributes to the control of salt and water metabolism in mammals [1], and specific uptake of 1251-labeled ovine PRL was seen in proximal tubular cells in rats [40]. In situ hybridization with oligonucleotide probes complementary to PRLRs and PRLRL indicated the localization of both receptor mRNAs in the kidney [13,141, although there was a large discrepancy in the distribution of signals.…”
Section: Discussionmentioning
confidence: 99%
“…which may be ascribed to (1) a direct antidiuretic action of prolactin, and (2) po tentiation of vasopressin and aldosterone action. However, prolactin preparations of various species are contaminated considera bly by neurohypophysial hormones, and this appears to be responsible for the renal action of prolactin [120], Nonetheless, spe cific prolactin receptors have been demon strated in the proximal tubules of mamma lian kidneys by both radioligand binding and autoradiographic techniques [84], High con centrations of prolactin also have been found in the epithelial cells of the proximal tubules, presumably as the result of trans port across the luminal membrane [34],…”
Section: Prolactinmentioning
confidence: 99%
“…A consequent increase in tubular reabsorptive area would contribute to the enhanced reabsorption observed here. Also of relevance may be the finding that prolactin can bind to tubular cells (Mountjoy, Cowden, Dobbie & Ratcliffe, 1980). Moreover Pippard & Baylis (1986) have shown that the hormone will stimulate Na'-K+-ATPase activity in the outer medulla of the rat kidney.…”
Section: Discussionmentioning
confidence: 99%